Peningkatan Keterampilan Menyimak Melalui Metode Bercerita di Kelas II SD Ayu Insan Usumo Edy Kabil Nongsa Batam - Sipahutar, Dorma Parulian; Ananda, Rizki; Sumianto, Sumianto (Institut Teknologi Pendidikan Indonesia, 2022)
This study aims to improve listening skills through the storytelling method. This type of research is Classroom Action Research (CAR) which is carried out collaboratively with class teachers. This research consists of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were second grade students of SD Ayu Insan Kusumo Edy Kabil Nongsa Batam, consisting of 12 students there were 7 male students and 5 female students. Methods of data collection using the technique of documentation, observation and written test. The data analysis technique used descriptive qualitative. The results showed that the use of the storytelling method could improve the listening skills of the second grade students of SD Ayu Insan Kusumo Edy Kabil Nongsa Batam. This is indicated by an increasein the number of students who achieve the Minimum Completeness Criteria (KKM) and anincrease in Classical. The percentage value of classical completeness is: Cycle I meeting I70.60% and cycle I meeting II 73.91% then increased to 75.33% for cycle II meeting I and84.88% in cycle II meeting II. Thus, the storytelling method can improve the listening skills of second grade students at SD Ayu Insan Kusumo Edy Kabil Nongsa Batam.